Direct and Indirect Effects of Cash Dividend Policies on Firms' Capital Accumulation in Selected Developed Markets - Mustafa Cayir; Nasuh Oguzhan Altay (Istanbul Business Research (IBR), 2021)
The effects of cash dividend policies on the capital accumulation of non-bank firms operating in The United States (S&P 500), The United Kingdom (FTSE 100), Japan (Nikkei 225), and France (CAC 40) have been investigated in this study. The dataset used in the study consists of annual observations between 2010 and 2015. Also, the data were retrieved from the Thomson Reuters database. The system in GMM is employed in the econometric estimations in this paper. “Total effect” of cash dividend policies on capital accumulation has been bisected as “direct” and “indirect” effects. In this study, we call the effect of the cash dividend policies on investments via financial and liquidity constraints as “direct effect” and the effect of the policies on the accumulation via market value and business reputation as “indirect effect”. Obtained results show that the indirect effect is positive, whereas the direct effect is negative. However , the magnitude of the direct effect is larger than that of the indirect. Therefore , the total effect of cash dividend policies on the accumulation of capital and investments is negative. The fact that movements in stock prices of firms have an effect on the capital accumulation has shown that the financial markets could affect real economic variables. Also, the results that the cash dividend policies positively affect the market value of firms are mounting evidence to the validity of Signalling and Information Content Approach and Bird in Hand Theory.
Keywords: 650; Capital Accumulation; Dividend Payouts; Financial Constraints; Market Value of Firms; System in GMM